Respon Pertumbuhan Bibit Anggrek Dendrobium sp. pada Saat Aklimatisasi terhadap Beragam Frekuensi Pemberian Pupuk Daun - DWIYANI, RINDANG (Agrotrop : Journal on Agriculture Science, 2014)
The aim of the experiment was to investigate the appropriate frequency of foliar fertilizer application of Hyponex and Gandasil D for the growth of seedlings of Dendrobium sp. at acclimatization stage. Various frequency of application for both foliar fertilizers were trialed, i.e. once in 5 days, once in 10 days, once in 15 days and control (without fertilizer). The results showed that the most appropriate frequency for the application of Hyponex and Gandasil D for seedlings of Dendrobium sp. was once in every 10 days.
Keywords: Dendrobium, Hyponex, Gandasil D